(untitled) (Eurasian Journal of Philology Science and Education, 2015)
“Divan-i-khykmet” known in all Turkic classical Middle Ages is systemically considered problems of history of scientific research of the outstanding collection of Kh.A. Yassavi in the present article". Especially great attention is paid to selfless life, to unique creativity, works and studying of language of the called medieval monument. Comprehensive investigation covers many materials, since 20th years of the last century and issued in the Soviet period. Works of modern turcologists are listed: R. Syzdykov, R. Berdibayev, E. Kazhybekov, M. Zharmukhamedov, M. Myrzakhmetuly, S. Dautuly, Z. Zhandarbek, A. Muminov, and also Turkish and other foreign researchers. Not less important question is also considered as investigation of hand-written versions of the original from the point of view of language, the difference in quantity khykmet is noted. Yasavivedeniye problems in a context of research of medieval development of Turkic literature: poetics, outlook and its influence on contemporaries.